IMPACT OF POTATO VALUE CHAIN SUPPORT PROJECT (PS-PVCSP) AMONG BENEFICIARIES IN PLATEAU STATE, NIGERIA - Baleri, Y. N.; Haruna, U.; Garba, M.; Abubakar, U. (Nigerian Journal of Agriculture and Agricultural Technology, 2023)
The study examined the impact of Potato Value Chain Support Project (PVCSP) among beneficiaries in Plateau State, Nigeria. A multi-stage sampling technique was used in selecting 390 respondents. Data were collected using structured questionnaire and were analysed using descriptive statistics and propensity score matching. The result revealed that, the major actors in the Irish potato value chain were producers (48.21%) and marketers (3.8%). Advisory services (42.5%) and inputs support (25.64%) were the major support provided by the project. The results further indicated a mean difference in the yield after the project of 9,916.78kg/ha and a mean income of ₦468,568.06 difference after the project. The major constraints to the project implementation were high cost of the fungicide promoted (57.2%), none participation of the right people in the project (54.6%), corruption (52.1%) and high cost of fertilizer (47.9%) among others. It was concluded that the PS-PVCSP had positive impact on the respondents’ income and yield. In addition, there was significant increase in potato cultivation after the project. Based on the result of this study, farm inputs such as fertilizer and other chemicals should be made available and affordable to farmers. Beneficiaries should be encouraged to form cooperative societies to access loans and procure inputs to enjoy economics of scale.